Low‐Dimensional Perovskites with Diammonium and Monoammonium Alternant Cations for High‐Performance Photovoltaics - Li, Pengwei; Liang, Chao; Liu, Xiao‐Long; Li, Fengyu; Zhang, Yiqiang; Liu, Xiao‐Tao; Gu, Hao; Hu, Xiaotian; Xing, Guichuan; Tao, Xutang; Song, Yanlin (Advanced materials (Weinheim), 2019)
Low‐dimensional Ruddlesden–Popper (LDRP) perovskites are a current theme in solar energy research as researchers attempt to fabricate stable photovoltaic devices from them. However, poor exciton dissociation and insufficiently fast charge transfer slows the charge extraction in these devices, resulting in inferior performance. 1,4‐Butanediamine (BEA)‐based low‐dimensional perovskites are designed to improve the carrier extraction efficiency in such devices. Structural characterization using single‐crystal X‐ray diffraction reveals that these layered perovskites are formed by the alternating ordering of diammonium (BEA2+) and monoammonium (MA+) cations in the interlayer space (B‐ACI) with the formula (BEA)0.5MAn PbnI3n+1. Compared to the typical LDRP counterparts, these B‐ACI perovskites deliver a wider light absorption window and lower exciton binding energies with a more stable layered perovskite structure. Additionally, ultrafast transient absorption indicates that B‐ACI perovskites exhibit a narrow distribution of quantum well widths, leading to a barrier‐free and balanced carrier transport pathway with enhanced carrier diffusion (electron and hole) length over 350 nm. A perovskite solar cell incorporating BEA ligands achieves record efficiencies of 14.86% for (BEA)0.5MA3Pb3I10 and 17.39% for (BEA)0.5Cs0.15(FA0.83MA0.17)2.85Pb3(I0.83Br0.17)10 without hysteresis. Furthermore, the triple cations B‐ACI devices can retain over 90% of their initial power conversion efficiency when stored under ambient atmospheric conditions for 2400 h and show no significant degradation under constant illumination for over 500 h. A new type of ACI perovskite is prepared through the alternating ordering of BEA2+ and MA+ cations in the interlayer space (B‐ACI). The high exciton extraction efficiency and a narrow distribution of quantum well widths of B‐ACI perovskite enable a device with a record efficiency of 17.39%. Furthermore, the devices show stronger resistance to humidity, heating, and light soaks than previous equivalents.